Neuroinflammation in a Rat Model of Tourette Syndrome - Zhongling, Ke; Yanhui, Chen; Guofeng, Chen; Yanyan, Liu (Frontiers in Behavioral Neuroscience, 2022)
Objective: Investigate the neuroinflammation of the IDPN-induced Tourette syndrome（TS）rats model to understand the possible mechanism of immune dysfunction in TS. Methods: Eighteen SD rats were randomly divided into normal control group, Tourette syndrome(TS) group, and TS+haloperidol group. The rat model of Tourette syndrome was constructed by intraperitoneal injection of IDPN, and the TS+haloperidol group was given haloperidol intervention. The behavioral, brain tissue cytokines (IL-6, TNF-a), and microglia activation of the three groups were assessed and compared. Results: The behavioral scores of rats in the TS group and TS+haloperidol group were higher than those in the normal control group (P<0.05), but the scores in the TS+haloperidol group were lower than those in the TS group (P<0.05). The levels of IL-6 and TNF-a in brain tissue were significantly higher in the TS group than in the normal control and TS+halopridol groups (P<0.05), while no significant differences were found between the normal control and TS+halopridol groups (P>0.05). The microglia significantly activated in the TS group and slightly activated in the TS+haloperidol group, which was considerably less than that in the TS group. Conclusion: The IDPN-induced TS rats had significant neuroinflammation, and the interaction between dopamine dysregulation and immune dysfunction may play a vital role in the pathogenic mechanisms of TS.